Environmental Security and Sustainable Land Use - with special reference to Central Asia - Vogtmann, Hartmut; Dobretsov, Nikolai; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Climate change, non-sustainable land management and the insufficient participation of the local population leads to land degradation problems in parts of the Altai Region, which includes China, Kazakhstan, Mongolia and the Russian Federation. This book presents important aspects of environmental security and sustainable land use in general and in particular for Central Asia, i.e. the environmental consequences of climate change; sustainable land use and regional development; sustainable development in mountain and steppe regions; beyond borders: Transboundary Biosphere Reserve "Altai" as an approach for regional development; landscape planning as an integrative tool for sustainable development; challenges and threats for environmental stability in Central Asia. A final recommendation in the area of sustainable development and land use as well as the proceeding efforts towards the establishment of the Transboundary Biosphere Reserve "Altai" and the implementation of landscape planning were set in the book as some of the main results of the meeting.
Environmental Consequences of Climate Change -- DESERTIFICATION OF MID-LATITUDE NORTHERN ASIA AND GLOBAL CHANGE PERIODICITY IN THE QUATERNARY -- REGIONAL CLIMATE AND ENVIRONMENTAL CHANGE IN CENTRAL ASIA -- THE REASONS AND CONSEQUENCES OF CLIMATE CHANGES -- CLIMATE CHANGE CONSEQUENCES IN STEPPE - FOREST TRANSITION ZONE IN MORAVIA -- SUSTAINABLE LAND USE AND REGIONAL DEVELOPMENT -- ASSESSMENT OF SUSTAINABILITY OF ECOLOGICAL - ECONOMIC SYSTEMS BY INDICATORS OF SUSTAINABLE DEVELOPMENT -- OVERVIEW OF NATO CCMS PILOT STUDY ON ENVIRONMENTAL DECISION-MAKING FOR SUSTAINABLE DEVELOPMENT IN CENTRAL ASIA -- EXPERIENCES IN THE STUDY OF LAND COVER TRANSFORMATION ON MEDITERRANEAN ISLANDS CAUSED BY CHANGE IN LAND TENURE -- STUDY OF SOILS MODIFIED WITH STRUCTURE FORMING AGENTS -- PROBLEMS OF INSTABILITY IN AGRARIAN NATURE MANAGEMENT AND FOOD SAFETY IN LARGE COUNTRIES OF CENTRAL ASIA -- SUSTAINABLE LAND USE AS A BASIS FOR A HEALTHY NUTRITION AND A CORNER STONE FOR REGIONAL DEVELOPMENT -- SUSTAINABLE DEVELOPMENT IN MOUNTAIN AND STEPPE REGIONS -- PROBLEMS OF SUSTAINABLE DEVELOPMENT OF MOUNTAINOUS REGIONS OF TAJIKISTAN -- IMPLICATION OF ENVIRONMENTAL LAW FOR MOUNTAIN PROTECTION IN CHINA -- ACTUAL ECOLOGICAL SITUATIONS IN THE TERRITORY OF MOUNTAIN REGIONS AND BIODIVERSITY PROBLEMS (THE CASE OF GEORGIA) -- NEW WAYS AND NEW FORMS OF LIMITED AND CONTROLLED NATURE MANAGEMENT IN THE STEPPE REGION OF NORTHERN EURASIA -- BEYOND BOARDERS: TRANSBOUNDARY BIOSPHERE RESERVE "Altai" AS AN APPROACH FOR REGIONAL DEVELOPMENT -- SUSTAINABLE LAND USE CONVERGENCE IN BORDER AREA IN CENTRAL EUROPE -- SUSTAINABLE DEVELOPMENT BEYOND ADMINISTRATIVE BOUNDARIES Case study: Rhön biosphere reserve, Germany -- THE LINKS BETWEEN POVERTY AND ENVIRONMENT: THE RATIONALE FOR ENVIRONMENTALLY SUSTAINABLE RESOURCE USE, WITH APPLICATION TO LAND MANAGEMENT IN THE ALTAI REGION -- CONDITIONS AND TRENDS IN NATURAL SYSTEMS OF THE ALTAI-SAYAN ECOREGION -- TRANSBOUNDARY BIOSPHERE TERRITORY "Altai": EXPERT EVALUATION FOR THE ESTABLISHMENT -- LANDSCAPE PLANNING AS AN INTEGRATIVE TOOL FOR SUSTAINABLE DEVELOPMENT -- LANDSCAPE PLANNING AS A TOOL FOR SUSTAINABLE DEVELOPMENT OF THE TERRITORY -- THE RUSSIAN SCHOOL OF LANDSCAPE PLANNING -- CHALLENGES AND THREATS FOR ENVIRONMENTAL STABILITY IN CENTRAL ASIA -- HISTORICAL EXPERIENCE AND ESTIMATION OF MODERN LAND TENURE OF THE INNER ASIA -- NO MAN'S LAND Environment Influences in Central Asian Security -- PHYSICAL - GEOGRAPHICAL CHARACTERISTICS OF THE ALTAI REGION -- NEW CHALLENGE OF THE MODERN CIVILIZATION AND GLOBAL ECONOMY IN THE NORTH OF THE WESTERN SIBERIA -- SUMMARY OF OTHER WORKSHOP LECTURES.
Keywords: ENVIRONMENTAL SCIENCES; REGIONAL PLANNING; CLIMATIC CHANGES; ENVIRONMENTAL MANAGEMENT; ECOLOGY; NATURE CONSERVATION; ENVIRONMENT; ENVIRONMENTAL MANAGEMENT; GEOECOLOGY/NATURAL PROCESSES; LANDSCAPE/REGIONAL AND URBAN PLANNING; NATURE CONSERVATION; CLIMATE CHANGE